BEHIND THE CHANGE OF THE NATIONAL EXAMINATION POLICY IN INDONESIA - Jailani, J. (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2021)
This study aimed to ï¬nd out the mapping of diï¬ƒculties in mathematics National Examination (NE) in Senior High School along with changes in NE policy in Indonesia in the last 10 years. Researcher conducted descriptive explorative analysis to ï¬nd out the scope of material, the absorption, and mapping the diï¬ƒculties faced by students in mathematics. Data analysis carried out by examining the data of each material and indicators. It grouped into two, namely low (<50%) and high absorption (â‰¥ 50%). The results showed that the overall absorption of the NE had decreased signiï¬cantly over the past 5 years (2013 to 2017). There did not ï¬nd out of diï¬ƒcult material before implementation of Curriculum 2013. However, the last 5 years (after the period of implementation Curriculum 2013) have found several diï¬ƒculties. Moreover, since 2015, almost all the materials on mathematics NE were categorized as diï¬ƒcult after the changing in the status of the NE (not a determinant factor of students’ graduation) and implementation the computer-based test. The diï¬ƒcult materials were probability, geometry transformations, space geometry, calculus, circles, linear programs, and statistics. Generally, the diï¬ƒculties were in narrative problem-solving questions or using real-world contexts. Also, the results showed non-cognitive impacts (students’ motivation) as the result of the policy changing, especially the status and technical implementation of the NE